ALTERNATIF PEMANFAATAN LIMBAH PERTANIAN SEBAGAI BAHAN BAKU PEMBUATAN PUPUK ORGANIK UNTUK MENDUKUNG PERTANIAN MAJU DAN BERKELANJUTAN - Darajah, Lale Imas Inda; Hakim, Arif Rahman; Supratman, Giana; Alfarisi, Muhammad Hilman; Dewi, Saskia Septina; Prastika, Yulia; Indriyani, Meidina; Adriana, Refia; Salsabila, Raden Roro Nisrinia; Dewi, Indah Komala; Sarjan, Muhammad (Jurnal Wicara, 2023)
Sembalun Bumbung Village is one of the villages in Sembalun District which has very good potential in the agricultural sector which can continue to be developed for the progress of the village. Therefore the existence of productive land must be managed optimally to maintain agricultural resources in a sustainable manner. However, this is faced with problems in the form of dependence of farmers on synthetic chemicals, especially on fertilization. The ease of obtaining chemical fertilizers instantly is a major factor in the use of these fertilizers, but it is feared that their continuous use can degrade the soil so that it will have an impact on production yields that are not optimal and reduce environmental quality. The Real Work Lecture (KKN) is then present as an effort to help the community to be able to independently get out of existing problems through the use of agricultural waste as a material that is used to be able to switch to using organic fertilizers. The implementation method used is in the form of observation, socialization, and direct manufacturing practice. The results obtained from this activity are that the community gains understanding and awareness regarding the use of organic fertilizers from agricultural waste to realize sustainable agriculture.